2010
DOI: 10.1038/ijo.2010.254
|View full text |Cite
|
Sign up to set email alerts
|

Intake of total, animal and plant protein and subsequent changes in weight or waist circumference in European men and women: the Diogenes project

Abstract: Background: As protein is considered to increase thermogenesis and satiety more than other macronutrients, it may have beneficial effects on prevention of weight gain and weight maintenance. Objective: The objective of this study is to assess the association between the amount and type of dietary protein, and subsequent changes in weight and waist circumference (WC). Methods: 89 432 men and women from five countries participating in European Prospective Investigation into Cancer and Nutrition (EPIC) were follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 25 publications
7
93
1
3
Order By: Relevance
“…We found that the association between protein intake and type 2 diabetes was strongest in obese women in contrast to prior research declaring weaker associations with increasing BMI (3). Our findings may be explained by the fact that higher total protein intake, and/or higher protein intake from animal sources, is associated with weight and weight gain (31,32). In our data, this effect would be stronger in women than in men.…”
Section: Discussioncontrasting
confidence: 40%
“…We found that the association between protein intake and type 2 diabetes was strongest in obese women in contrast to prior research declaring weaker associations with increasing BMI (3). Our findings may be explained by the fact that higher total protein intake, and/or higher protein intake from animal sources, is associated with weight and weight gain (31,32). In our data, this effect would be stronger in women than in men.…”
Section: Discussioncontrasting
confidence: 40%
“…At the nutrient level, we are suspecting the high protein intake (~19 E % in the highest quintile of PC4- Table 2) combined with a low intake of dietary fiber (~11 g/day) being responsible for the positive associations with weight gain. Despite the convincing evidence from RCT and physiological studies that a high protein intake is beneficial for weight loss and control in the short-term, longer-term and/or large-scale observational studies have reported the opposite [29][30][31]. The effects of dietary nutrient mixtures on appetite and weight control are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The participants in the DiOGenes trial [5], showing better weight loss maintenance with a high protein intake, were matched on gender, diet and body characteristics in the observational Danish Diet, Cancer and Health (DCH) cohort study, showing a tendency to weight gain with greater protein intake [6].…”
Section: Methodsmentioning
confidence: 99%
“…Randomized, controlled trials (RCTs) have suggested an overall beneficial effect of high-protein diets on weight loss and weight maintenance after weight loss [4], [5]. In contrast, large-scale, long-term observational cohort studies have shown that greater protein intake is associated with weight gain [6], [7]. Although results from RCTs and observational studies often reach similar results [8][12], the sometimes conflicting findings make the formation of health recommendations difficult.…”
Section: Introductionmentioning
confidence: 99%